Thirty years of the Academic Journal (ARLA). Issue 1 (5th March 2018) - Ogliastri, Enrique; Pombo, Carlos; Salgado, Elvira
Abstract : Purpose: The purpose of this paper is to introduce the anniversary issue marking 30 years of academic publication. Design/methodology/approach: This anniversary issue contains 12 articles from 11 countries and 17 academic institutions which present literature reviews, meta-analyses, and novel studies. It also contains testimonials about the history of the journal from Enrique Ogliastri (Editor and/or Director between 1998 and 2018), Elvira Salgado (Editor between 2002 and 2013), and Carlos Pombo (Chief Editor, 2013 to the present). Findings: The history of the journal may be divided into five stages: first, the foundation at the Universidad de Chile (1988-1998); second, the move to the Universidad de los Andes (Bogotá) and the preparation of a proposal to the Institute of Scientific Information (ISI) for inclusion among the scientific journals of the world (1999-2004); third, a period of consolidation in Latin America (2004-2007); fourth, the acceptance of the journal in ISI and the development of an electronic platform with free access to the journal (2008-2013); and fifth, the entry of the Emerald group as editorial partner (2013-2018). Originality/value: The 12 articles present literature reviews, meta-analyzes, and novel studies. Abstract : Propósito: El propósito de este editorial es presentar el tema del aniversario. Diseño/metodología/enfoque: Se publican doce artículos provenientes de once países y 17 instituciones académicas. Se presentan los testimonios de Enrique Ogliastri (editor y/o director entre 1998 y 2018), Elvira Salgado (Editora entre 2002 y 2013), y Carlos Pombo (jefe editorial 2013-2018). Hallazgos: Se publican doce artículos provenientes de once países y 17 instituciones académicas. Se presentan los testimonios de Enrique Ogliastri (editor y/o director entre 1998 y 2018), Elvira Salgado (Editora entre 2002 y 2013), y Carlos Pombo (jefe editorial 2013-2018). La historia de la revista de CLADEA se podría dividir en cinco etapas: la fundación en la Universidad de Chile (1988-1998); pasó a cargo de la Universidad de los Andes (Bogotá), un período de puesta a punto para presentar al Institute of Scientific Information (ISI) la solicitud de ser analizada e incluida entre las revistas científicas del mundo (1999-2004); el período de consolidación en América Latina (2004-2007); la aceptación en ISI y el desarrollo de una plataforma electrónica de acceso libre a la revista (2008-2013); y el ingreso del grupo Emerald como socio editorial (2013-2018). Originalidad/valor: Los 12 artículos presentan revisiones de literatura, metanálisis y estudios novedosos